The Use of Bark Water Extracts of Eucalyptus camaldulensis to Control the Snail Host Bulinus truncates of Urinary Schistosomiasis - Salman, S. A.; Ibrahim, K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study is a contribution to determine the effect of bark water extracts of the common trees of Eucalyptus camaldulensis to control the snail intermediate host (Bulinus truncatus) of urinary Schistosomiasis in Iraq. It was found that the lethal concentrations of bark phytochemicals to this snail were ranging from 10gm/l to 50gm/l.The effect of bark extracts was very remarkable during the first 24 hours.